(untitled) (UCC Law Journal, 2025)
Intellectual property rights generally put right holders in a dominant position in the marketplace, and rightly so, as their rights grant them some time-limited monopolies. Competition policy, on the other hand, seeks to prevent the abuse of a dominant position by regulating competition to ensure a fair market. In view of the aforesaid, there appears to be a conflict between the two legal frameworks. There are, however, some attempts at responding to the concerns of competition policy in intellectual property laws. The paper recognizes the absence of a comprehensive competition regime in Ghana. Employing a doctrinal approach to data collection and analysis, the paper reviews the points of convergence and divergence between intellectual property laws and competition policy in Ghana. The paper briefly explores the successful and challenging resolution of IP and competition law conflicts in some African countries. The paper concludes that the attempts at addressing competition concerns by the use of intellectual property legal regimes are not enough. The paper calls for proactive steps to be taken toward the passage of a comprehensive competition legal regime to ensure a fairer market, thereby promoting free trade in Africa.